El rol de la biblioteca de la Unidad Educativa del Milenio “El Tambo” en el proceso de formación de lectores literarios - Labanda Paccha, Rosario del Cisne (2023)
The aim of this research is to analyze the role of the library at "El Tambo" School in the development of reading habits among students. To achieve this objective, specific goals were formulated related to the activities and processes carried out by the school library and the reading habits of students. Data collection involved the use of observation sheets, interviews, and a survey administered to a sample of 140 students. Drawing upon these instruments, various strategies were devised to enhance the role of the school library in nurturing literary readers, which can be considered and implemented at "El Tambo" Unidad Educativa del Milenio. The most salient findings indicate that the school library is being attended to during hours inconvenient for students, and that the reading hour is not effectively utilized by subject teachers. Administrative staff lack resource management skills, and the teacher responsible for the school library, who belongs to the Area of Cultural and Artistic Education, requires greater organization to promote reading and the utilization of literary works intended for students. There is a need for reflection on educational projects and their sustainability throughout the academic year, incorporating reading activities and workshops.